PERSPEKTIF PONDOK PESANTREN DALAM PENDIDIKAN KARAKTER UMMAT - Mukhtar Nuhung (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2017)
This paper is raining to photograph the system of boarding school education, what are the advantages and disadvantages, and how the pattern of character education development in boarding school. The research method used is Library Research. Data collection is done by collecting data related to the discussion of some books then give a description and then concluded. The results of this study obtained first datahwa, Three Pillars of education (Family, School, community) is in the boarding into a systematic unity in the process of education and implemented in the daily activities of students / learners. Second, the pattern of character education development in pondok pesantren begins with characteristic leadership pattern and characteristic environment. Kiai, coach and Ustadz as role models in the example by the santri in the whole activity. Patterns of independence, simplicity, togetherness, a sense of responsibility, discipline, and regular worship become daily habits and behaviors, and a culture of learning that is built. Thirdly, the shortage of the pesantren cottage system is still busy with its routine and has not been thought of to be involved in technological development. As a suggestion, the authors sagat dreaming in the boarding school system of pesantren which is engaged in economy, industry and Technology.